THE RELATIONSHIP BETWEEN PEER SOCIAL SUPPORT AND ADJUSTMENT AMONG STUDENTS WITH DISABILITIES AT SEBELAS MARET UNIVERSITY - Ristia Dwi Susanti; Sugini Sugini; Mahardika Supratiwi (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2024)
This research aims to determine the existence of a relationship between peer social support and adaptation among students with disabilities at Sebelas Maret University. The subjects of this study were 30 students with disabilities at Sebelas Maret University. The sampling technique used total sampling. This study employed peer social support and adaptation scales for data collection. Data analysis utilized Pearson Product Moment correlation. The results showed a correlation coefficient of 0.587 with p = 0.001 (p < 0.05), indicating a positive and significant relationship between peer social support and adaptation among students with disabilities at Sebelas Maret University, Surakarta.